Epidemiological profile of women with endometriosis: a retrospective descriptive study - Jéssica Vilarinho Cardoso; Daniel Escorsim Machado; Mayara Calixto da Silva; Plínio Tostes Berardo; Renato Ferrari; Maurício Simões Abrão; Jamila Alessandra Perini (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to describe the epidemiological and clinical profile of women with endometriosis and to determine the association with the prognostic characteristics of the disease. Methods: retrospective descriptive study involving 237 women attended at two referral hospitals for endometriosis, between 2011 and 2017. Associations between groups were estimated using logistic regression models. Results: most women (65.4%) were of reproductive age (29-39 years), with a body mass index in the range of 18.5-24.9 kg/m2 and a high prevalence (23-81%) of symptoms of the disease, with 49.5% being infertile. The average time of diagnosis was 5 years. Ovarian endometrioma and/or deep infiltrative endometriosis (DIE) were the most frequent type of endometriosis (87%), and 59% of patients were in the III/IV stage of the disease. Approximately 87% of women with surgical diagnosis were aged over 30, married (70%) and had lower parity. Dyspareunia was negatively associated with superficial endometriosis. Infertility was positively associated with age (30-39 years) and DIE in the uterine tubes; dysmenorrhea with DIE in the uterosacral ligament; cyclic intestinal complaints with DIE in the rectosigmoid and intestine, and with DIE classification and III/IVstage. Conclusions: knowing the epidemiological and clinical profile of Brazilian women with endometriosis can help in diagnosis and treatment planning.